Phonological status, not voice onset time, determines the acoustic realization of onset f0 as a secondary voicing cue in Spanish and English. (March 2015) - Dmitrieva, Olga; Llanos, Fernando; Shultz, Amanda A.; Francis, Alexander L.
Abstract: The covariation of onset f 0 with voice onset time (VOT) was examined across and within phonological voicing categories in two languages, English and Spanish. The results showed a significant co-dependency between onset f 0 and VOT across phonological voicing categories but not within categories, in both languages. Thus, English short lag and long lag VOT stops, which contrast phonologically, were found to differ significantly in onset f 0. Similarly, Spanish short lag and lead VOT tokens are phonologically contrastive and also differed significantly in terms of onset f 0. In contrast, English short lag and lead VOT stops, which are sub-phonemic variants of the same phonological category, did not differ in terms of onset f 0. These results highlight the importance of phonological factor in determining the pattern of covariation between VOT and onset f 0. Highlights: We examine onset f 0 as function of voicing/VOT. We examine onset f 0 across and within phonological voicing categories. We examine onset f 0 and voicing in Spanish and English. Effect of VOT on onset f 0 is present if VOT is phonologically contrastive. Effect of VOT on onset f 0 is absent within phonological categories.